If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -116 + -6x = 3x + 100 Reorder the terms: -116 + -6x = 100 + 3x Solving -116 + -6x = 100 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -116 + -6x + -3x = 100 + 3x + -3x Combine like terms: -6x + -3x = -9x -116 + -9x = 100 + 3x + -3x Combine like terms: 3x + -3x = 0 -116 + -9x = 100 + 0 -116 + -9x = 100 Add '116' to each side of the equation. -116 + 116 + -9x = 100 + 116 Combine like terms: -116 + 116 = 0 0 + -9x = 100 + 116 -9x = 100 + 116 Combine like terms: 100 + 116 = 216 -9x = 216 Divide each side by '-9'. x = -24 Simplifying x = -24
| 5a+4b=11 | | 4x+12-2-6x-8=10-3x+3 | | 3(6m+3)= | | 100=s+r+g | | -18m-4+4m-14= | | 5x^2y^3-180y=0 | | 3=2x^2-4x+5 | | 4(h-1)=2h+8 | | 48b=322 | | 0.19xX=105.75 | | v-(4-5x+2v)= | | -11-y=14 | | 12t-1=-5 | | 3x(-x+9)= | | 12q^2+11qd-15d^2=0 | | 4(2+7p)= | | y=-1x-151+4 | | 12=4b-36 | | 2/5x2 | | 8x+-3=9 | | 4-1(3p-2)=p-10 | | -2(4x)+3(9x)= | | -4=-x^2-10x-29 | | X^(2/5) | | 2x^2-30x-225=0 | | (21b-8)-5(4b+1)=-4 | | 3m^2+20m+12=0 | | 10+4s=2r+g | | 225+-90= | | 2a=15+5a | | 1/4(4x) | | 4x+6x+3+8=7x+5+2x |